Discursive dimension of the construction and the circulation of knowledge connected with the issue of foreign language teacher education within the Polish glottodidactic community - LIMBACH, CHRISTIANE (Glottodidactica, 2017)
Up to the present day, only a few articles have dealt with the didactics of liaison interpreting. This particular one aims to contribute to a didactic basis, offering a practical approach to consecutive liaison interpreting for the German-Spanish language pair. It will place a special focus on role plays and preliminary practical exercises. With the help of role plays, students are able to identify, acquire and apply the skills and strategies necessary for liaison interpreting. Moreover, role plays offer students the opportunity to observe and evaluate the complete process of interpreting. Giving students the task of fictitious interpreting assignments with directed progression of difficulties, which the students prepare beforehand and which are simulated in the lessons, creates a certain dynamic in class. This motivates students to successfully approach any difficulties when acquiring interpreting competences and then to overcome them.